China’s Aviation Industry During the COVID-19 Pandemic - So, Simon MS; Wang, Reese R (International Journal of Social and Administrative Sciences, 2022)
This paper discusses the impact of the COVID-19 pandemic on the aviation industry in China. The major challenges facing the Chinese aviation industry is the reduction in passenger demand. In addition, the financial pressure facing Chinese airlines continues to pose unique challenges to the competitiveness of the aviation industry. Our PESTLE analysis shows that the Chinese government needs to be more proactive in developing solutions to help the aviation industry. MOST analysis also supports the aviation industry’s goal of achieving global leadership through strategic alliances, aircraft investments, technological innovations, and improved consumer service. From the SWOT analysis, the Chinese aviation industry can leverage its innovative technologies and government financial support to gain a competitive advantage and meet consumer demands. Therefore, the challenges facing the Chinese aviation industry under the impact of the COVID-19 pandemic can be mitigated by recommendations that align with China’s financial, social, and economic frameworks.